1994
DOI: 10.1177/096120339400300204
|View full text |Cite
|
Sign up to set email alerts
|

Review: Anti-Endothelial Cell Antibodies: a Need for Standardization

Abstract: Twenty years have passed since the original description of the anti-endothelial cell antibodies (AECA). It is widely acknowledged that the presence of circulating autoantibodies against endothelial cells surface antigens, found in a number of patients with connective tissue disease and vasculitis, is one of the driving mechanisms for the observed vascular injury and might be an important factor in initiating the pathogenesis of vascular abnormalities. AECA data regarding the prevalence, technical problems, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 55 publications
3
12
0
Order By: Relevance
“…5% of patients with SLE and demonstrated its antibody specificity through absorption with A5498-8 epithelial cells (Adler et al, 1994;. However, we confirmed that positivity of AECA is not necessarily high in patients with aPA and is somewhat higher in the aPA-negative group.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…5% of patients with SLE and demonstrated its antibody specificity through absorption with A5498-8 epithelial cells (Adler et al, 1994;. However, we confirmed that positivity of AECA is not necessarily high in patients with aPA and is somewhat higher in the aPA-negative group.…”
Section: Discussionsupporting
confidence: 61%
“…To confirm the specificity of AECA (Adler et al, 1994;Youinou et al, 1995), 100 ml serum samples judged AECA-positive were mixed with 10 ml of A5498-8 cells (10 5 /ml) (Biolab, U.S.A.) or 10 ml of buffer and incubated for 1 h at 37ЊC. AECA was measured to compare the difference in OD of cell-absorbed and unabsorbed serum.…”
mentioning
confidence: 99%
“…Thus, efforts to find a serologic marker of BD have been made in order to diagnose BD before the fulfillment of diagnostic criteria. AECA has been detected in various inflammatory diseases, including BD [9][10][11][12]. But there have been few studies focused on the characteristics of the antigen recognized by AECA.…”
Section: Discussionmentioning
confidence: 99%
“…As a heterogeneous group of antibodies against various proteins on the surface of endothelial cells, anti-endothelial cell antibody (AECA) has been detected in various immune-mediated diseases [9,10]. AECA has also been demonstrated in the sera of patients with BD [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…AECA has been demonstrated in the serum of patients with systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), mixed connective tissue disease, scleroderma, and dermatomyositis, as well as patients with Wegener's granulomatosis (WG), primary retinal vasculitis, Kawasaki disease, acute hemolytic uremic syndrome, diabetes mellitus, organ transplants, hypoparathyroidism, multiple sclerosis, thrombotic thrombocytopenic purpura, angioedema, and Buerger's disease (5,6). AECA has also been demonstrated in the serum of BD patients (7)(8)(9)(10) and has been associated with disease activity and vasculitis symptoms (6,7).…”
mentioning
confidence: 99%